Bioconjugating Thiols to Poly(acrylamide) Gels for Cell Culture Using Methylsulfonyl Co‐monomers. (6th January 2016) - Farrukh, Aleeza; Paez, Julieta I.; Salierno, Marcelo; del Campo, Aránzazu
Abstract: Poly(acrylamide) P(AAm) gels have become relevant model substrates to study cell response to the mechanical and biochemical properties of the cellular microenvironment. However, current bioconjugation strategies to functionalize P(AAm) gels, mainly using photoinduced arylazide coupling, show poor specificity and hinder conclusive studies of material properties and cellular responses. We describe methylsulfonyl‐containing P(AAm) hydrogels for cell culture. These gels allow easy, specific and functional covalent coupling of thiol containing bioligands in tunable concentrations under physiological conditions, while retaining the same swelling, porosity, cytocompatibility, and low protein adsorption of P(AAm) gels. These materials allow quantitative and standardized studies of cell‐materials interactions with P(AAm) gels.